2019
DOI: 10.1111/avj.12797
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mortality and severe morbidity requiring euthanasia in captive Tasmanian devils (Sarcophilus harrisii) in Tasmania

Abstract: Background Devil facial tumour disease (DFTD) is a contagious cancer causing marked population declines in wild Tasmanian devils. In response to this threat, a captive insurance population has been established. This study investigated causes of death in captive Tasmanian devils. Methods Clinical and laboratory records of captive Tasmanian devils held in seven Tasmanian captive facilities were analysed for cause of death or severe morbidity requiring euthanasia. Results Neoplasia was found to be the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Interestingly, non-DFTD neoplasia is a major cause of mortality and morbidity of devils in captivity. A recent study reported that over an eight-year period in Tasmania, non-DFTD cancers accounted for 43% of deaths in captivity [134]. Of these cancer-related mortalities, cutaneous lymphomas, cutaneous round cell tumours, squamous cell carcinomas and adenocarcinomas were most common.…”
Section: Inherent Predisposition and Immune Functionmentioning
confidence: 99%
“…Interestingly, non-DFTD neoplasia is a major cause of mortality and morbidity of devils in captivity. A recent study reported that over an eight-year period in Tasmania, non-DFTD cancers accounted for 43% of deaths in captivity [134]. Of these cancer-related mortalities, cutaneous lymphomas, cutaneous round cell tumours, squamous cell carcinomas and adenocarcinomas were most common.…”
Section: Inherent Predisposition and Immune Functionmentioning
confidence: 99%
“…Cancer incidence in domestic animals is generally less than 10% ( N = 202,277) ( 3 ). However, two studies performed 40 years apart reported that greater than 40% of Tasmanian devils develop spontaneous, often severe neoplasia in their lifetime ( 5 , 7 ). Devils are also unique because they are affected by two of the three known naturally occurring transmissible cancers in vertebrate species ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tasmanian devils are listed as endangered and a captive insurance population has been set up in response to the threat of devil facial tumour disease (DFTD). Veterinary care is critical and our first study this issue aimed to assess the causes of deaths or euthanasia in captive Tasmanian devil facilities …”
Section: Wildlife and Zoosmentioning
confidence: 99%